Kill or bee killed - Marts, Jennie (Marts, Jennie. Bee keeping mystery., 2024)
With the murder of a celebrity host putting a buzzkill on the annual Bee Festival when her best friend is accused of the crime, Bailey and her Granny Bee are determined to find the truth, save the festival and catch the real killer before they sting someone else.